The Role of Nutritional Factors in Maintaining the Health of Pregnant Women - Rakhmatillayevna, Rakhmonova Dildor (American Journal of Bioscience and Clinical Integrity, 2025)
This article is devoted to studying the content of proteins, fats, carbohydrates, and their energy value in the daily diet of pregnant women aged 18–29 living in rural areas of the Kashkadarya region. According to the obtained results, the amount of protein in the daily diet of the examined women was relatively lower than the recommended norm, while the amounts of fats and carbohydrates were found to be close to or significantly higher than the norm.